Chan insights and oversights: an epistemological critique of the Chan tradition - Faure, Bernard (Princeton University Press, 1993)
Cover Page -- Half-title Page -- Title Page -- Copyright Page -- Dedication Page -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- Chan as Secondary Orientalism -- The Cultural "Encounter Dialogue -- Comparison, Counterpoint, Intertwining -- Part One -- Chapter One: Chan/Zen in the Western Imagination -- Missionary Accounts -- Buddhism and Quietism -- Chan and Indian Mysticism -- The Apostle Bodhidharma -- Claudel and Buddhism -- Chapter Two: The Rise of Zen Orientalism -- Suzuki's Zen -- The Western Critics of Suzuki -- Nishida and the Kyoto School -- Chapter Three: Rethinking Chan Historiography -- Places and People -- The Rise of Chan Historiography in Japan -- The Cost of Objectivism -- The Teleological Fallacy -- Writing Chan History -- Chapter Four: Alternatives -- The Structural Approach -- The Hermeneutic Approach -- Toward a Performative Scholarship -- Part Two -- Chapter Five: Space and Place -- Chan and Local Spirits -- From Place to Space -- Chan Insights and Di-visions -- Chapter Six: Times and Tides -- Conflicting Models -- Dogen and His Times -- The Ritualization of Time -- Chapter Seven: Chan and Language: Fair and Unfair Games -- On the Way to Language -- Poetical Language in Chan -- How to Do Things with the Koan -- Chapter Eight: In-scribing/De-scribing Chan -- A Qualified Anti-intellectualism -- Chan Logocentrism -- Orality in Chan -- Chan as a Kind of Writing -- Another Differend -- Chan Rhetoric -- Chapter Nine: The Paradoxes of Chan Individualism -- The Western Configuration of the Self -- Early Buddhist Conceptions -- Chinese Conceptions -- The Individual and Power -- Solitaire I Solidaire -- Epilogue -- Glossary -- Bibliography -- Index.